Catalyst tolerance to SO2 and water vapor of Mn based bimetallic oxides for NO deep oxidation by ozone. Issue 40 (10th May 2017) - Lin, Fawei; Wang, Zhihua; Shao, Jiaming; Yuan, Dingkun; He, Yong; Zhu, Yanqun; Cen, Kefa
Abstract : Improving the catalyst stabilities under different conditions (water vapor, SO2, both water vapor and SO2 ) is important for industrial applications regarding catalytic NO deep oxidation by ozone. Abstract : Improving the catalyst stabilities under different conditions (water vapor, SO2, both water vapor and SO2 ) is important for industrial applications regarding catalytic NO deep oxidation by ozone. In this paper, Ce–Mn/SA and Fe–Mn/SA catalysts were selected to investigate the stabilities. The results showed that the Ce–Mn/SA exhibited excellent stability and resistance to SO2, while the Fe–Mn/SA only displayed excellent stability without moisture and SO2 . Almost a 50% drop in efficiency was observed after deactivation by water vapor and water vapor together with SO2 for the two catalysts. The Fe–Mn/SA displayed inferior resistance to SO2 . After stability testing with water vapor, the surface area, pore volume, and average pore diameter all decreased. The low adsorption energy of the H2 O molecule resulted in the superior adsorption of water vapor, which occupied large amounts of active sites. XPS results showed that the ratio of Mn 4+ and chemisorbed oxygen decreased after deactivation. Mn 4+ favors NO oxidation, while Mn 3+ is favorable for ozone decomposition. Therefore, better performance in NO deep oxidation by ozone requires relative balance distribution between Mn 4+ and Mn 3+ . Interestingly, the TPD results showed that the NO desorption peak was unaffected and even increased a lot after water vapor stability testing. This could be attributed to the nitrates, formed by the N2 O5 and H2 O in liquid phase, that were adsorbed on the catalyst surface prior to NO, which contributes to a bigger NO desorption peak with lower NO adsorption ability. The trace of sulfate formed after SO2 stability testing was verified from TPD and TGA results, but it was not observed from the FTIR spectra, indicating the sulfate species formed during the ozonation process may not exist on the catalyst surface.